Security analysis - Popa, Claudiu (Henry Stewart Talks, 2019)
Security analysis, Security testing, Vulnerability audits, Compliance audits, Risk assessment, Reporting, Remediation, Budgeting, Confidentiality, integrity and availability (CIA)